2008
DOI: 10.1055/s-2008-1039395
|View full text |Cite
|
Sign up to set email alerts
|

Die isokinetische Kraftleistungsfähigkeit der Rumpfmuskulatur von Patienten mit chronischen Rückenschmerzen

Abstract: Lumbar isokinetic strength and the influence of age, bodyweight and testing velocity in patients with chronic low back pain in comparison with persons without pain. Lumbar isokinetic strength parameters of 80 patients with chronic low back pain and 70 persons without pain were compared and the influence of age, bodyweight and testing velocity was evaluated. The patients with chronic low back pain showed less strength than the persons without pain. All parameters of extension discriminated between the two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The intensity of the pain depends on the degree of contraction of the fascia that maintains the normal shape of the body, muscles, nerves and skeleton (10). Relying solely on drug formulations and injections as a therapeutic approach to improving back pain can limit flexibility and reduce core strength and spinal durability, resulting in recurrence of pain (11). Fascia Relaxation Exercise, a nerve and fascia system recommended by the National Academy of Sports Medicine (NASM), SMR uses foam rollers and braces to inhibit irritable muscle fibers and to reduce the emotional or physical effects of the autonomic nervous system, such as vasodilation and increased muscle contraction.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the pain depends on the degree of contraction of the fascia that maintains the normal shape of the body, muscles, nerves and skeleton (10). Relying solely on drug formulations and injections as a therapeutic approach to improving back pain can limit flexibility and reduce core strength and spinal durability, resulting in recurrence of pain (11). Fascia Relaxation Exercise, a nerve and fascia system recommended by the National Academy of Sports Medicine (NASM), SMR uses foam rollers and braces to inhibit irritable muscle fibers and to reduce the emotional or physical effects of the autonomic nervous system, such as vasodilation and increased muscle contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Low back pain (LBP) is associated with altered motor control and muscle activity. A number of studies have shown a link between LBP and delayed muscle onsets [1], lower level of motor variability [2], reduced muscle activation of the trunk, increased stiffness [3], lower muscle force [4], changes in muscles' voluntary activity [5] and higherordered movement capacities, such as gait [6,7]. Interestingly, although all of these behavioural features have their own underlying physiological changes (e.g.…”
Section: Introductionmentioning
confidence: 99%